Pendidikan Islam di Tengah Masyarakat Multikultural - Hakim, Muhammad luqman (Qouman : Jurnal Pendidikan dan Studi Islam, 2024)
Multiculturalism is an understanding of the reality of diverse societies. Where multiculturalism is a response to diverse and plural social facts, so that a humanist, democratic and just order of life can ultimately be achieved. Multiculturalism recognizes and glorifies differences in equality both individually and culturally. The research design carried out was a literature review. In this research, data was obtained from books and journals related to Islamic education in a multicultural society.Based on research results, multicultural education is an educational strategy that is applied to all types of education, both formal and non-formal. Islam really respects religious differences in social life. Islam really respects differences in religion, ethnicity, nation and these differences must be seen as God's will. Strategies for understanding diversity by looking at multiculturalism include; Understanding religious diversity, understanding language diversity, building gender sensitivity, understanding social status diversity, understanding ethnic diversity and appreciating differences in abilities